2006
DOI: 10.3201/eid1210.051015
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits, Risks, and Cost-Effectiveness of Influenza Vaccination of Children

Abstract: Vaccinating children aged 6–23 months, plus all other children at high-risk, will likely be more effective than vaccinating all children against influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 35 publications
2
138
1
Order By: Relevance
“…In general, the studies suggested that vaccination of adolescents who were not at high risk was not cost-saving in nonpandemic years and that significant investment would be required for vaccinating adolescents who were not at high risk against influenza. [21][22][23] Although vaccinating adolescents at high risk of complications has been consistently found to be more costeffective (or cost-beneficial) than vaccinating those not at high risk, several unknowns could change the overall picture. For example, it is not known if a recommendation for routine vaccination for all adolescents might improve coverage rates for adolescents at high risk.…”
Section: Influenza Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…In general, the studies suggested that vaccination of adolescents who were not at high risk was not cost-saving in nonpandemic years and that significant investment would be required for vaccinating adolescents who were not at high risk against influenza. [21][22][23] Although vaccinating adolescents at high risk of complications has been consistently found to be more costeffective (or cost-beneficial) than vaccinating those not at high risk, several unknowns could change the overall picture. For example, it is not known if a recommendation for routine vaccination for all adolescents might improve coverage rates for adolescents at high risk.…”
Section: Influenza Vaccinementioning
confidence: 99%
“…One of these studies reported cost-effectiveness estimates 21 (Table 3 and Appendix 3), 2 studies reported only cost/ benefit ratios, 22,23 and 1 study reported a different outcome (cost per healthy LYS) that was not used for comparisons. 24 (Appendix 3).…”
Section: Influenza Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…[292][293][294][295] A comparison of the economics of vaccinating children with TIV or LAIV found similar cost savings between the two vaccines, with an increased cost for both vaccines for older versus younger children. [296] Analyses of vaccination programs targeting pregnant women show that it is cost-effective. [297][298][299] Vaccination of pregnant women with additional comorbidities was found to be cost-saving.…”
Section: Cost Effectiveness Of Seasonal Influenza Vaccinationmentioning
confidence: 99%
“…13,14,36 With the recent expansion of the VSD, the project is well positioned to conduct RCA studies and traditional VSD analyses on new vaccines being introduced for teenagers and young adults. Although the majority of VSD studies focus on hypotheses related to vaccine safety, the VSD has also demonstrated its ability to conduct studies on vaccine coverage, 37-41 disease incidence, [42][43][44][45][46][47][48][49] methodology, 14,36,50 cost-effectiveness, [51][52][53] and medical informatics. 10,54 As described previously, the computerized vaccination records have been shown to be of high quality, 55 whereas the accuracy of computerized records to determine medical outcomes varies.…”
Section: Discussionmentioning
confidence: 99%